PREPARATION AND EVALUATION OF SURFACE MODIFIED NANOPARTICLES OF CALCIUM PHOSPHATE AS EXTRACT CARRIER - BANERJEE, SRITOMA; SEN, KALYAN K. (International Journal of Applied Pharmaceutics, 2020)
Objective: The aim of this study was to develop, optimize and characterize carbohydrate coated calcium phosphate nanoparticles of Chelidonium majus L. extract along with carried out in vivo study to observe activity in the liver. Methods: Surface modified calcium phosphate nanoparticles of Chelidonium majus L. extract were developed and optimized. Extract loading and particle size were the two responses, effects on which were analyzed. Characterization studies, in vitro extract release and in vivo distribution studies were carried out. Also in vivo histopathological analysis was carried out to observe effects of extract loaded nanoparticles in liver of wistar albino rats in paracetamol, rifampicin-isoniazid, cisplatin and carbon tetrachloride-induced hepatotoxicity. Results: Pareto chart and surface response curve indicated that sonication time, the concentration of lactose and concentration of extract were important factors affecting particle size and extract loading. ANOVA was performed and obtained data pointed out that model was significant for both responses. Particle size and zeta potential results indicated the stability of prepared nanoparticles along with extract was loaded (37.22 %) satisfactorily on coated cores. Characterization studies indicated no interaction between the components and also extract release demonstrated diffusion-controlled mechanism. These extract loaded nanoparticles were largely found in the liver than heart, lungs. Hepatoprotective activity of nanoparticles of the extract was confirmed by correlating histopathology results of normal, toxic, silymarin treated, extract-treated and formulation treated groups. Conclusion: Lactose coated nanoparticles of calcium phosphate proved to be excellent carriers of plant extract. These nanoparticles efficiently targeted liver and generated cellular protective action in hepatic damage.